Code Switching In Twitter Of Alexander Thian: A Synactic Analysis - Silalahi, Gabriella Mauretania; Tetty, Morada (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This thesis analyses the types, the use, and the reason why Code-switching are used in Alexander Thian on his tweets. This study used Poplack and Hoffman’s theory in order to answer the problems and used a descriptive qualitative method to analyze. There are three types in Poplack Theory and seven reasons why code-switching used in Hoffman Theory. The source of data is Twitter and there are 50 tweets found as the data. Those tweets in Alexander Thian’s twitter were examined to categorize them into distinct categories. This study found that Alexander Thian uses three types of code-switching in his twitter account, namely tag-switching (4%), inter-sentential switching (42%), and intra-sentential switching (54%).  While for the reasons, the Code switching were mostly used in talking about particular topic twenty-six tweets (52%), quoting somebody else six tweets (12%), being emphatic about something ten tweets (20%), interjection four tweets (8%), intention of clarifying the speech content two tweets (4%), and expressing group identity two tweets (4%).